Autonomia parkatêjê para preservar sua língua nativa: me ikwy tekjê ri - SILVA, Maria de Nazaré Moraes da (Universidade Federal do Pará, 2017)
After the 1988 Constitution, formal education in Brazil suffered many changes. Nowadays, schools tend to adapt their actions to the current educational paradigm, and indigenous communities take a stand in this matter. One said community is the Parkatêjê, inhabitants of the Mãe Maria Reservation Area, in Pará. This paper, based on published materials, gathers information about the initiative of this community to preserve its culture. It also brings data about the implementation of formal education among indigenous people and about autonomy, a phenomenon related to current pedagogical practices. This text highlights the fact that Indigenous Education has not yet matured with regards to the preservation of native languages and suggests that ethnographical studies should be carried out in indigenous schools. The text also aims at helping to spread the word about the Parkatêjê experience in valuing its own culture.